Navigating the Low-Code Landscape: A Comparison of Development Platforms - Kirchhof, Jorg Christian; Jansen, Nico; Rumpe, Bernhard; Wortmann, Andreas (2023 ACM/IEEE International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2023)
Low-code development is a software-development paradigm that can reduce the conceptual gap between application domain problem expertise and software engineering solution expertise. Hence, it might be a vital means to reduce the impact of the world-wide scarcity of software-developers. Consequently, many different low-code development platforms (LCDPs) have surfaced in the last 5-10 years, which domain experts must understand to chose the best-possible LCDP for their applications. This choice is not made restricting to front-end features of these LCDPs, but also to back-end features, which the domain experts are usually less familiar with. To support domain experts in making this decision, we have investigated popular LCDPs for features relevant to domain experts. Our findings aim to guide these domain experts, but also researchers in better understanding the landscape of LCDPs.